Hyperlipidemia is associated with lower risk of poststroke mortality independent of statin use: A population-based study. Issue 2 (February 2017) - Yeramaneni, Samrat; Kleindorfer, Dawn O; Sucharew, Heidi; Alwell, Kathleen; Moomaw, Charles J; Flaherty, Matthew L; Woo, Daniel; Adeoye, Opeolu; Ferioli, Simona; de los Rios La Rosa, Felipe; Martini, Sharyl; Mackey, Jason; et al.
Background: Although statin therapy is associated with reduced stroke and mortality risk, some studies report that higher lipid levels are associated with improved outcomes following ischemic stroke. Aims: We examined the association of hyperlipidemia (HLD) combined with statin therapy on all-cause mortality in stroke patients. Methods: All stroke patients in the Greater Cincinnati Northern Kentucky region of ∼1.3 million were identified using ICD-9 discharge codes in 2005 and 2010. Stroke patients with and without HLD were categorized based on their reported statin use at baseline or discharge into three groups: no-HLD/no-statins, HLD/no-statins, and HLD/on-statins. Cox proportional hazards model was used to estimate the risk of mortality at 30 days, 1 year, and 3 years poststroke. Results: Overall, 77% (2953) of the 3813 ischemic stroke patients were diagnosed with HLD and 72% ( n = 2123) of those patients were on statin medications. The mean age was 70.0 ± 14.6 years, 56% were women, and 21% were black. In adjusted analyses, the HLD/no-statins group showed 35% (adjusted hazard ratio (aHR) = 0.65, 95% CI: 0.46–0.92), 27% (aHR = 0.73, 95% CI: 0.59–0.90), and 17% (aHR = 0.83, 95% CI: 0.70–0.97) reduced risk of mortality at 30 days, 1 year, and 3 years, respectively, poststroke, compared with no-HLD/no-statins group. The HLD/on-statins group showed an additional 17% significant survival benefit at 3 years poststroke compared with HLD/no-statins group. Conclusions: A diagnosis of HLD in ischemic stroke patients is associated with reduced short- and long-term mortality, irrespective of statin use. Statin therapy is associated with significant, additional long-term survival benefit.